The Catholic doctrine of non-Christian religions : according to the Second Vatican Council - Ruokanen, Miikka. (Studies in Christian Mission, 1992)
In the Second Vatican Council (1962-65) the Catholic Church for the first time recognized non-Christian religions as entities which the Church should respect and with which Christians should enter into dialogue. There are, however, conflicting views in Catholic interpretations of Conciliar theology: to what extent did the Council see other religions as means to salvation? The author offers The Catholic Doctrine of non-Christian Religions according to the Second Vatican Council as the first comprehensive and analytic piece of research on Conciliar teaching concerning the nature of other faiths. His study is based on the original Latin and covers Conciliar and pre-conciliar documents, with special focus on the Declaration on the relation of the Church to Non-Christian religions, (Nostra aetate). In his detailed and careful analysis Ruokanen demonstrates that Vaticanum Secundum understood non-Christian religions as naturally good entities, part of human culture. Religions express in many ways and to varying degrees the natural cognition of God and of natural moral law. Except for Judaism, they do not, however, possess the status of being considered channels of divine revelation or salvific grace. The seeds of truth present in other faiths must be purified and perfected by the fullness of grace and truth given in Christ and entrusted to the Church.